National Culture and Organizational Learning - Nebojša Janićijević (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The paper studies the influence of national culture on organizations' preferences regarding selection amongst forms of organizational knowledge and character of organizational learning processes. The goal of the paper is to generate some new hypothesis about the possible influence of national culture on organizational learning based on Hofstede's concept of cultural dimensions and Nonaka's concept of forms and processes of organizational learning. Previous studies have shown that it is reasonable to assume that individualism and masculine values within national culture imply preference in favour of explicit knowledge and externalization and combination as forms of organizational learning. Collectivism and feminine values in national culture imply preference toward tacit knowledge along with socialization and internalization as forms of organizational learning.
Keywords: M14; M16; 330; national culture; knowledge management; organizational learning; crosscultural management